Health Information System Krama Bali Sejahtera Public Services Innovation Improves Denpasar Community's Trust For Healthy Behavior Through Adaptation Of New Habits - Putu Vierda Lya Suandari; I Made Dhita Prianthara (Jurnal Manajemen Kesehatan Indonesia, 2022)
The government in providing public services to the community is required to be effective and efficient, therefore it is continuously expected to be able to innovate services in a better direction to improve quality. Service quality is an important thing that determines public trust in public services to be able to realize community participation by increasing knowledge, trust and developing community habits regarding the concept of healthy behavior in adopting new habits and closer government relations with the community. This study aims to determine the description of public service innovations in Denpasar City in increasing public confidence to behave healthily in adapting to new habits, especially in the community in Denpasar City. Data analysis in this study used Partial Least Square (PLS) with a sample of 200 respondents who accessed the measured SIK-KBS. The results of the SIK-KBS public service innovation assessment show that the Bali Provincial Government has a positive assessment with a score of 75.3 and is in the BB (innovative) public service innovation qualification level. Based on this value, it is known that the SIK-KBS public service innovation that has been carried out in Denpasar City in improving information access services has been innovative and able to increase public confidence in healthy behavior which has a significant positive effect as seen from the t-statistic value > 1.96.